2017
DOI: 10.1177/0149206317731519
|View full text |Cite
|
Sign up to set email alerts
|

Play at Work: An Integrative Review and Agenda for Future Research

Abstract: Play has gained increasing interest among progressive-minded managers as an important driver of motivation and productivity in work contexts. Despite its popularity in contemporary organizations, there is little consensus in the academic literature about the role of play in the workplace. This review organizes and synthesizes the current state of knowledge of play at work in order to gain a more comprehensive understanding of what play at work is, when individuals engage in play at work, and the effects of wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(127 citation statements)
references
References 84 publications
4
93
0
3
Order By: Relevance
“…We believe that having effective, evidence‐based tools to enhance or mitigate the consequences of perfectionism in the workplace should be helpful for organizations and their members. For example, scholars and organizational leaders should consider the utility of microbreak or playful activities as a form of energy management strategy to allow individuals with perfectionistic tendencies to recover and repair negative consequences of sustained work (Demerouti, Bakker, Geurts, & Taris, ; Petelczyc, Capezio, Wang, Restubog, & Aquino, ). Kim, Park, and Headrick () found that microbreaks involving relaxation (e.g., stretching and walking around the office), social (e.g., chatting with colleagues on nonwork topics and messaging family or friends), and cognitive (e.g., reading books or newspapers) activities improved job performance via positive affect of workers with low work engagement.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…We believe that having effective, evidence‐based tools to enhance or mitigate the consequences of perfectionism in the workplace should be helpful for organizations and their members. For example, scholars and organizational leaders should consider the utility of microbreak or playful activities as a form of energy management strategy to allow individuals with perfectionistic tendencies to recover and repair negative consequences of sustained work (Demerouti, Bakker, Geurts, & Taris, ; Petelczyc, Capezio, Wang, Restubog, & Aquino, ). Kim, Park, and Headrick () found that microbreaks involving relaxation (e.g., stretching and walking around the office), social (e.g., chatting with colleagues on nonwork topics and messaging family or friends), and cognitive (e.g., reading books or newspapers) activities improved job performance via positive affect of workers with low work engagement.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…The first essential aspect of play is that the activity is carried out with the goal of fun and/or challenge (e.g., Csikszentmihalyi, 1975;Mainemelis & Ronson, 2006). The focus on fun and challenge explains why play activities are often voluntary and process-focused, and why individuals are intrinsically motivated to engage in play (Petelczyc et al, 2018). The second feature of play is that it requires an enthusiastic and in-the-moment attitude.…”
Section: Play During Workmentioning
confidence: 99%
“…We selected employees from this organization, as this organization is typical of a small to medium sized tech-start up in Canada, specializing in both software and hardware. Specifically, knowledge sharing is particularly important in this organization [38], and employees in this organization commonly engage in workplace fun activities [7,8], such as trips, sporting events, celebration of achievements, and fun team building activities (i.e., paintball, trivia)…”
Section: Samplementioning
confidence: 99%
“…Indeed, these social interactions are essential to promote knowledge exchange [6]. Despite this rationale and the fact that a plethora of organizations are working towards injecting more fun activities into the workplace [5,7,8,9], research has not yet empirically examined how the interpersonal interactions that are inherent in fun activities may facilitate positive knowledge management behaviors (KMBs).…”
Section: Introductionmentioning
confidence: 99%